1982
DOI: 10.1182/blood.v59.1.76.bloodjournal59176
|View full text |Cite
|
Sign up to set email alerts
|

Primary thrombocythemia: clonal origin of platelets, erythrocytes, and granulocytes in a GdB/GdMediterranean subject

Abstract: A patient with primary thrombocythemia, who was heterozygous for glucose-6-phosphate dehydrogenase deficiency (GdB/GdMed), was investigated to test for the clonal origin of this myeloproliferative disorder. In order to assess somatic cell mosaicism in various tissues, we have made use of the different rate of utilization of 2-deoxyglucose- 6-phosphate, an analog of glucose-6-phosphate, by normal glucose-6- phosphate dehydrogenase and by the Mediterranean variant: the results demonstrate that essential thromboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Granulocytes (PMN) and mononuclear cells (FH) were purified from peripheral blood according to standard methods [2]. Monocytes were removed from the FH fraction by adhesion to plastic culture dishes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulocytes (PMN) and mononuclear cells (FH) were purified from peripheral blood according to standard methods [2]. Monocytes were removed from the FH fraction by adhesion to plastic culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…The myeloproliferative disorders (MPD) are a diverse group of hemopoietic diseases characterized by abnormal proliferation of a subset of marrow elements. Previous studies have shown that they are clonal diseases that arise in a multipotent hemopoietic stem cell [1,2]. Recent findings however have suggested a variability in the dominance of the neoplastic clone in some MPD patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of such corresponding features at presentation, apart from the presence of ring sideroblasts, makes it unlikely that our three patients represent a more chronic form of this condition. The use of the genetic marker G6PD has been important in showing the myeloproliferative diseases polycythaemia rubra Vera (Adamson et al 1976), chronic granulocytic leukaemia (Barr & Fialkow 1973), primary thrombocythaemia (Gaetani et al 1982) and agnogenic myeloid metaplasia (Jacobson, Salo & Fialkow 1978) to be clonal disorders of a pluripotent marrow stem cell. Similar use of this marker has shown PASA likewise to be a clonal disorder, clonal characteristics being demonstrated in both myeloid and lymphoid cell lines (Prchal et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The patient was heterozygous for G6PD (Gd B/Gd Med) by analysis of a skin biopsy and hair follicle specimens. Haemopoietic cell populations from heparinized peripheral blood were purified as described elsewhere (Gaetani et al, 1982) and tested for G6PD mosaicism with the 2deoxy glucose-6-phosphate (2dG6P) technique, based on the relative different affinity of the B enzyme and the Mediterranean variant for 2dG6P, an analogue of the normal substrate G6P (Ferraris et al, 1981(Ferraris et al, , 1984. The sensitivity of this method allows the detection of a minor enzyme component as small as 5%.…”
Section: Methodsmentioning
confidence: 99%